Utilizing Social Media Analytics to Demonstrate Program Impact - Brosius, LeAnn; Cless, Adam (My University, 2018)
The application of social media within programs has grown exponentially over the past decade and has become a popular way for programs to engage and reach their stakeholders and inform engagement efforts. Consequently, organizations are utilizing data analytics from social media platforms as a way to measure impact. These data can help programs understand how program objectives, progress, and outcomes are disseminated and used (i.e., through discussions, viewing of content, following program social media pages).
Keywords: Evaluation; Social media use; Social media analysis